PENGETAHUAN DAN SIKAP MAHASISWA DALAM KEPUTUSAN PEMBELIAN PRODUK HALAL - rosidi, ali (Universitas Muhammadiyah Semarang, 2018)
Consumers must be more critical in making decisions before buying food products. This study aims to determine the relationship between knowledge with student attitudes in purchasing decisions for halal products. The population of this study were the students of Muhammadiyah University of Semarang. The variables that studied were the level of knowledge of halal food and the attitude of decisions for buying halal products. This type of research was observational with a cross sectional design. The tool that used were questionnaires and data analysis by using two stages, namely univariate and bivariate (Simple Linear Regression). The results of the study revealed that the student's knowledge of halal food was the most moderate category at 40.2% and positive positive attitude was 53.6%. Based on statistical tests, it can be concluded that there is a relationship between knowledge and attitude in buying halal products.